Overture to revolution the 1787 Assembly of Notables and the crisis of France's old regime - Hardman, John (Oxford University Press, 2010)
A clear analytical narrative of the French Assembly of Notables of 1787. John Hardman brings together the various facets of this seminal assembly, which have generally been considered in isolation (the king, the royal council, the Notables, the role of Necker, and of the public) into a single integrated account.